If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2y + x = 11 Reorder the terms: x + 2y = 11 Solving x + 2y = 11 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. x + 2y + -2y = 11 + -2y Combine like terms: 2y + -2y = 0 x + 0 = 11 + -2y x = 11 + -2y Simplifying x = 11 + -2y
| 100+-7x=58 | | -4y-13=5y+24 | | (x^2+6)*(7-x)= | | 32x^2+96x+72=0 | | 10x^2+1=2 | | 2x+x-8=x-5 | | 7*X+Y=64.26 | | 5x=3y+b | | 5t+45=705-2t | | 16-7w=24 | | 125x+7=13+x | | 3h-2(3h-1)=4h+37 | | -(7-g)= | | 20x-19=20+10x | | p^2+18p+47=-9 | | .75x+x=-3+.5x | | 2x-4(2x+1)=3x-22 | | 4z+15=-3z+8 | | 4w-8=6w-4 | | 6y+(6+y)= | | -17x+20x=x | | 81p^2-100=0 | | 14x-3x^2=16 | | -3[14-5(x+4)]=x | | 9b-(12+6b)+3= | | 3(a-4)=4a+6 | | 5(35)+0.1m=5(25)+0.25m | | 4x+3x+6= | | 2[7-4(3+2)]=x | | 3(s)+6(a)=375 | | (42+63)*42= | | 3xs+6xa=375 |